Critical survey of graphic novels : history, theme, and technique - Beaty, Bart; Weiner, Stephen, 1955- (Critical survey of graphic novels., 2019)
This book offers in-depth insight into themes and topics related to graphic novels. It provides insight into various aspects of the industry, from craftsmanship such as lettering, inking, and illustration styles, to the production and distribution of graphic novels and the significance and history of comic book conventions.